2022
DOI: 10.7554/elife.66869
|View full text |Cite
|
Sign up to set email alerts
|

Complex effects of kinase localization revealed by compartment-specific regulation of protein kinase A activity

Abstract: Kinase activity in signaling networks frequently depends on regulatory subunits that can both inhibit activity by interacting with the catalytic subunits and target the kinase to distinct molecular partners and subcellular compartments. Here, using a new synthetic molecular interaction system, we show that translocation of a regulatory subunit of the protein kinase A (PKA-R) to the plasma membrane has a paradoxical effect on the membrane kinase activity. It can both enhance it at lower translocation levels, ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Finally, leading edge PKA activity can be induced in relatively non-motile HeLa cells by simply asymmetrically recruiting RII regulatory subunit to the plasma membrane. This study used a rapamycin inducible recruitment system to recruit R subunit to the plasma membrane and found that at moderate levels of recruitment, PKA activity was increased, and the cell would move toward the rapamycin gradient ( LaCroix et al, 2022 ). At high levels of R subunit recruitment, PKA activity was ultimately inhibited.…”
Section: Location Location Locationmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, leading edge PKA activity can be induced in relatively non-motile HeLa cells by simply asymmetrically recruiting RII regulatory subunit to the plasma membrane. This study used a rapamycin inducible recruitment system to recruit R subunit to the plasma membrane and found that at moderate levels of recruitment, PKA activity was increased, and the cell would move toward the rapamycin gradient ( LaCroix et al, 2022 ). At high levels of R subunit recruitment, PKA activity was ultimately inhibited.…”
Section: Location Location Locationmentioning
confidence: 99%
“…Recalling the study using rapamycin-inducible recruitment of RII subunit, this manipulation had differing effects on PKA activity and directional cell migration depending on the level of induction ( LaCroix et al, 2022 ). Moderate amounts of recruitment of R subunit to the membrane led to increased and sustained PKA activity there whereas high levels ultimately inhibited PKA activity ( LaCroix et al, 2022 ).…”
Section: Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…While these studies are highly suggestive, there are advantages to live-cell imaging, which allows for a comprehensive assessment of the spatially guided signaling dynamics in individual cells. Recent studies have highlighted this potential by exploring intracellular G-protein dynamics, and spatially resolved ERK1/2 signaling 15 16 , PKA 38 , and AMPK nuclear signaling 39 , defining the critical spatial control of kinases, where adaptor and substrate accessibility drives their functional roles. While it is well known that p38 has a central role in the regulation of both cytosolic and nuclear proteins 2 , 3 , direct analysis of the spatiotemporal p38 dynamics has not been carried out.…”
Section: Discussionmentioning
confidence: 99%